Study on the adsorption mechanism of benzoylurea insecticides onto modified hyperbranched polysilicon materials. Issue 48 (4th August 2020) - Liu, Chaoran; Huang, Xiaodong; Meng, Zilin; Qian, Heng; Liu, Xinya; Lu, Runhua; Zhou, Wenfeng; Gao, Haixiang; Xu, Donghui
Abstract : Several hyperbranched polysilicon with different end group modifications were prepared, and the adsorption mechanism of benzoylureas onto the obtained materials were investigated based on the density functional theory and adsorption studies. Abstract : Several hyperbranched polysilicon (HBPS) materials with different end group modifications were designed and synthesized and the structures were characterized. The modified HBPS polymers were applied to the adsorption of benzoylurea insecticides (BUs). The binding mode and binding energy between the HBPS and BUs were quantified and the results of an adsorption kinetics study and an adsorption thermodynamics experiment were verified by calculation and mutual verification. The adsorption mechanism of BUs onto HBPS was also discussed. The theoretical results show that the most effective way to combine the adsorbent and BUs is via hydrogen bonding when the end group is an amino group. Moreover, the most effective combination when the end group is β-cyclodextrin is the interaction of the BUs with the interior of the cavity to form a host–guest coating. The theoretical results of other end group-modified HBPS materials were also obtained and verified by adsorption experiments. In this work, an experimental method for obtaining the binding mode by theoretical calculations and then verifying it according to adsorption experiments was established.